2019
DOI: 10.1002/app.48304
|View full text |Cite
|
Sign up to set email alerts
|

Castor oil‐based polyols with gradually increasing functionalities for biopolyurethane synthesis

Abstract: In this research, castor oil‐based polyols with gradual increasing functionalities were prepared using thiol‐ene photo click reaction. The polyols were prepared by facile and efficient photo‐click reaction using thiols with different number of hydroxyl groups. The polyols were successfully synthesized using a modified bio‐oxygen demand (BOD) reactor and their structures were characterized. The hydroxyl number of the prepared polyols gradually increased depending on the thiol used for preparation. The increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 48 publications
5
11
0
Order By: Relevance
“…The hydroxyl values of CO, COM, and COT were analyzed according to the ASTM D1957-86 standard and the measured values were 152, 259, and 366 mg KOH/g, respectively, which correspond to the values in our previous report [26]. These results confirmed that the synthesis of adequate modified polyols was required for the preparation of PU foams was successful.…”
Section: Characterization Of Polyolssupporting
confidence: 82%
See 2 more Smart Citations
“…The hydroxyl values of CO, COM, and COT were analyzed according to the ASTM D1957-86 standard and the measured values were 152, 259, and 366 mg KOH/g, respectively, which correspond to the values in our previous report [26]. These results confirmed that the synthesis of adequate modified polyols was required for the preparation of PU foams was successful.…”
Section: Characterization Of Polyolssupporting
confidence: 82%
“…It contains a hydroxyl group at the C-12 position in nature, which allows it to be utilized in PU production [ 25 ]. However, the successful commercialization of PU produced from CO is limited by the poor mechanical properties of the foam and low productivity, which are attributed to the inherent characteristics of CO, such as low hydroxyl value, low reactivity of secondary OH groups, and steric hindrance [ 26 ]. Recently, several studies have focused on overcoming these drawbacks through the modification of castor oil by epoxidation [ 27 ], transesterification [ 28 ], ozonolysis [ 29 ], and radical addition [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous study, we reported the thermal decomposition behavior of PU prepared using CO-based multifunctional polyols and various diisocyanates. It has been confirmed that there is no significant effect on the second stage thermal decomposition behavior for vegetable oil-based PUs regardless of the type of polyol and diisocyanate used 12 . The final step is due to the complete degradation of the remainders of the second stage.…”
Section: Characterization Of Fgo-pu Nanocomposites Structural Analysmentioning
confidence: 81%
“…[10] To increase the renewable content, bio-PUs are mainly obtained by reacting diisocyanates and polyols resulting from functionalization of vegetable oils extracted from various plants (rapeseed, soybean, palm, etc.). [11][12][13][14][15][16] Natural vegetable oils contain saturated and unsaturated triglycerides but do not contain hydroxyl groups, with the exception of castor and lesquerella oils. However, functionalization of the carbon-carbon double bond through epoxidation followed by oxirane ring-opening, [17][18][19] hydroformylation followed by hydrogenation, [20] ozonolysis, [20] or thiol-ene coupling [21] affords a wide range of biobased polyols, enabling reactions with diisocyanates to get bio-PUs.…”
Section: Introductionmentioning
confidence: 99%